Sleep variability and nighttime activity among Tsimane forager‐horticulturalists. Issue 3 (10th July 2018) - Yetish, Gandhi; Kaplan, Hillard; Gurven, Michael
Abstract: Objectives: A common presumption in sleep research is that "normal" human sleep should show high night‐to‐night consistency. Yet, intra‐individual sleep variation in small‐scale subsistence societies has never been studied to test this idea. In this study, we assessed the degree of nightly variation in sleep patterns among Tsimane forager‐horticulturalists in Bolivia, and explored possible drivers of the intra‐individual variability. Methods: We actigraphically recorded sleep among 120 Tsimane adults (67 female), aged 18–91, for an average of 4.9 nights per person using the Actigraph GT3X and Philips Respironics Actiwatch 2. We assessed intra‐individual variation using intra‐class correlations and average deviation from each individual's average sleep duration, onset, and offset times ( ɛ ¯ ). Results: Only 31% of total variation in sleep duration was due to differences among different individuals, with the remaining 69% due to nightly differences within the same individuals. We found no statistically significant differences in Tsimane sleep duration by day‐of‐the‐week. Nightly variation in sleep duration was driven by highly variable sleep onset, especially for men. Nighttime activities associated with later sleep onset included hunting, fishing, housework, and watching TV. Conclusions: In contrast to nightly sleep variation in the United States being driven primarily by "sleeping‐in" on weekends, Tsimane sleep variation, while comparable to that observed in the United States, was driven by changing "bedtimes, " independent of day‐of‐the‐week. We propose that this variation may reflect adaptive responses to changing opportunity costs to sleep/nighttime activity.